Loves me, loves me not: The Museum of Broken Relationships scene analysis - Benceković, Sara (My University, 2014)
﻿The Balkan region is known for its historical climate of turbulent social relations; thus, public spaces that consecrate shared experiences of grief and loss come as no surprise. One such space, however, has experienced astonishing growth in its fame and popularity, not just as a renowned cultural landmark, but as a significant Croatian cultural export. The Museum of Broken Relationships is filled with unremarkable everyday objects donated by lovers who associate them with their past relationships. The value of these objects is not necessarily utilitarian, or aesthetic, but symbolic: they represent the emotions of remorse and pain elicited by breakups. This paper is an account of the objects, stories, and narratives found in the Museum of Broken Relationships. It considers the Museum a lens through which people can scrutinize the meaning of love in their everyday lives and consequently re-shape their identities. It looks into the Museum’s transformative potency as a spiritual and sacred space that offers hope in times of despair, fosters disorientation and chaos, and offers visitors an opportunity to confirm or reject their previous perspectives on love.
PUBLISHED
Keywords: Museums; Love; Material culture; Identities in Transformation; LOVE; Material Culture; museums